Does Bowel Preparation Improve the Performance of Rectal Water Contrast Transvaginal Ultrasonography in Diagnosing Rectosigmoid Endometriosis?. (24th September 2018) - Ferrero, Simone; Barra, Fabio; Stabilini, Cesare; Vellone, Valerio Gaetano; Leone Roberti Maggiore, Umberto; Scala, Carolina
Abstract : Objectives: The primary objective of the study was to compare the performance of the rectal water transvaginal ultrasonography (RWC‐TVS) with and without bowel preparation (BP) in diagnosing rectosigmoid endometriosis. The secondary objectives were to compare the performance of the 2 exams in estimating infiltration of the mucosa, length of the largest rectosigmoid nodules, distance of the nodules from the anal verge, and presence of multifocal disease. Methods: This prospective study included patients with pain symptoms and intestinal complaints suggestive of endometriosis. Patients underwent RWC‐TVS with and without BP within an interval of 1 week to 2 months. Two independent and blinded gynecologists performed the exams. The results of the 2 exams were compared with surgical and histologic findings. Results: A total of 155 patients were included in the study; 92 patients had rectosigmoid endometriosis. There was no significant difference in the performance of RWC‐TVS with or without BP in diagnosing rectosigmoid endometriosis ( P = .727). There was no significant difference in the performance of RWC‐TVS with or without BP in diagnosing infiltration of the mucosa ( P = .424) and multifocal disease ( P = .688), in estimating the main diameter of the largest nodule ( P = .644) and the distance between the more distal rectosigmoid nodule and the anal verge ( P = .090). The patients similarly tolerated the 2 exams ( P = .799). Conclusions: Bowel preparation does not improve the performance of RWC‐TVS in diagnosing rectosigmoid endometriosis and in assessing the characteristics of these nodules.